(untitled) (Sociedade e Estado, 2002)
Starting with an overview of possible solutions to the problem of social order, the author presents a non-acritical reconstruction of Edmund Husserl’s transcendental phenomenology of intersubjectivity as a sympathetic alternative to Habermas’s theory of communicative action. By means of a detailed analysis of the concept of empathy (Einfühlung), he shows that Husserl’s phenomenology of intersubjectivity offers a triple foundation of the sciences. As a warrant of the objectivity of the world, it grounds the natural sciences; as a presupposition of sociality, it founds the social sciences; as mediated by culture, it grounds the social sciences as human sciences.